2020
DOI: 10.1186/s12891-020-03588-5
|View full text |Cite
|
Sign up to set email alerts
|

Modified Bunnell suture repair versus bundle-to-bundle suture repair for acute Achilles tendon rupture: a prospective comparative study of patients aged <45 years

Abstract: Background This study aimed to compare the operative outcome of percutaneous repair (modified Bunnell suture technique) versus open repair (bundle-to-bundle suture technique) of acute Achilles tendon rupture. Methods Seventy-two consecutive patients who underwent surgical treatment of Achilles tendon rupture were evaluated in this prospective study. Thirty-six patients were treated using the bundle-to-bundle suture technique (group A), and 36 patients were treated using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Patients report mean scores of 31-56 at three months [10,11,13] and 54-87 at six months [11,[32][33][34][35][36][37][38][39][40][41][42][43][44]. One year after the rupture, the mean score has been reported to be 74-91 [11,24,32,33,35,36,[38][39][40][42][43][44][45][46][47][48][49][50][51][52][53][54][55], and it does not appear to appreciably improve further thereafter [14,15,24,39,42,46,47,[56][57][58][59]…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%
“…Patients report mean scores of 31-56 at three months [10,11,13] and 54-87 at six months [11,[32][33][34][35][36][37][38][39][40][41][42][43][44]. One year after the rupture, the mean score has been reported to be 74-91 [11,24,32,33,35,36,[38][39][40][42][43][44][45][46][47][48][49][50][51][52][53][54][55], and it does not appear to appreciably improve further thereafter [14,15,24,39,42,46,47,[56][57][58][59]…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%
“…Recent evidence has found that distinct surgical variations and variations in postoperative protocols result in different degrees of tendon elongation [8, 18, 27, 30, 40, 72, 86]. Further, post-treatment tendon elongation has been associated with lower patient-reported outcomes scores and reduced plantarflexion strength [28, 79, 91]. For these reasons, surgeons must largely rely on direct RCT evidence of patient-reported outcomes rather than pooled comparisons when putting the findings of our study into context.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has found that distinct surgical variations and variations in postoperative protocols result in different degrees of tendon elongation [8,18,27,30,40,72,86]. Further, post-treatment tendon elongation has been associated with lower patient-reported outcomes scores and reduced plantarflexion strength [28,79,91] Similarly, return to work and sport analyses were not performed because of very low evidence quality and poor assessment of the endpoints in question. Inconsistency in returnto-sport reporting has been previously noted by other researchers [3,44,66], although studies have found no difference between open repair, MIS repair, and functional rehabilitation [23,60,66].…”
Section: Limitationsmentioning
confidence: 99%
“…The open and the percutaneous techniques are both safe and effective in repairing the ruptured AT, and both afford the same degree of restoration of clinical, ultrasound, and isokinetic patterns [ 57 ]. Nevertheless, the main advantages of percutaneous repair include reduced cutaneous complications, use of analgesics, and operation times; day surgery procedures; fewer deep infections; faster recovery, enhancing overall patient compliance with improved of AOFAS scores; and lower healthcare costs [ 41 , 55 , 58 , 59 , 60 ]. As Ma and Griffith and Tenolig satisfied most of these advantages in our patient groups, another implication of this study is that they can be considered preferable to open repair in managing subcutaneous ruptures of AT also in non-professional sports practicing adults, confirming the results of previous reports [ 57 , 61 ].…”
Section: Discussionmentioning
confidence: 99%